Identifikasi Deteksi Tepi Pada Pola Wajah Menerapkan Metode Sobel, Roberts dan Prewitt - Novia Wulan Dari (Bulletin of Information Technology (BIT), 2022)
The face is a part of the body that is generally useful as a recognition tool. Faces that are visible to the naked eye look similar but each person's face has a different pattern. Facial pattern is one of the factors that can show the characteristics of a person's face that can affect the characteristics of that person's race. Several researchers suggested facial types based on facial morphological indices. To find out the difference in the pattern of the human face, image processing can be done with edge detection. Edge (edge) is the edge of the surface of an object. The edge of an image is a different boundary between two areas in an image object. Edge detection is the process of finding the outline of an image object. The purpose of detecting edges is to classify objects in the image and useful for analyzing subsequent images. In detecting images on facial patterns, among others, by applying the Sobel, Roberts and Prewitt methods. From the detection results, it can be concluded that the Sobel method produces image edges that show a clearer pattern and are in accordance with the original image